The Role of Regional Cultural Week in an Effort to Maintain the Existence of Traditional Games as the Nation's Cultural Heritage in the Modern Era - Bambang Yuniarto; Ibnu Umar Fahdri; Aldi Salam; Ade Nur; Aliya Masrurah (International Journal Labs, 2023)
In writing this journal will be discussed on the topic entitled